First Record: A Stem and Bulb Plant Parasitic Nematode at Garlic Area Centre Temanggung, Central Java, Indonesia with Species Reference to Ditylenchus dipsaci - Siwi Indarti; Arif Wibowo; Siti Subandiyah; Miftahul Ajri (Universitas Gadjah Mada, 2018)
A survey to investigate the stem and bulb plant parasitic nematode at one of garlic area centre, in Temanggung, Central Java, Indonesia was conducted from Januaryto February 2018. Infected plant with specific symptoms, morphological and morphometric characters both of female and male of adult nematodes were used to describe a A1 quarantine plant parasitic nematode Ditylenchus dipsaci. Seven from nine observed locations were postively infected with population in average 2.67 nematodes per 100 g of soil and 2.67–189.33 per bulb. This is the first report of D. dipsaci from Indonesia and consequently further investigations were needed to know their distribution and also to confirm the origin of the nematode. IntisariSurvei keberadaan nematoda parasit batang dan umbi dilakukan pada bulan Januari–Februari 2018 pada satu sentra penangkaran bawang putih di Temanggung, Jawa Tengah, Indonesia. Tanaman terinfeksi dengan gejala serangan yang spesifik, karakter morfologi dan morfometri nematoda betina dan jantan dewasa dipergunakan dalam identifikasi Ditylenchus dipsaci yang merupakan nematoda parasit tanaman yang termasuk OPTK A1 (Organisme Pengganggu Tanaman Karantina A1) di Indonesia. Sebanyak tujuh dari sembilan lokasi yang diamati mengindikasikan positif sebagai daerah sebaran nematoda tersebut dengan populasi rata-rata 2,67 ekor per 100 gram tanah dan 2,67–189,33 nematoda per umbi. Laporan pertama tentang nematoda D. dipsaci ini membawa konsekuensi perlunya penelitian lebih lanjut untuk mengetahui daerah sebaran dan juga konfirmasi dari mana nematoda tersebut berasal.